ANALISIS DISIPLIN KERJA PT ISS INDONESIATERHADAP KINERJA KARYAWAN - Mr Mukrodi (Universitas Pamulang, 2018)
The purpose of this research is to know the phenomenon and the conclusion about the influence to the three independent variables on employee performance at PT ISS Indonesia.This research is associative with quantitative approach. The sample used in this study were 150 respondents. Data analysis technique used in this research is validity test, reliability test, normality test, multicolinearity test, heteroscedasticity test, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, t test and F count test.The results of the study as follows, there is a positive influence and significant work discipline on employee performance at PT. ISS Indonesia. This can be proven from simple linear regression value Y = 13,602+0,592X correlation value equal to 0,642, coefficient determination equal to 41,2%, and value t arithmetic 10,184> t table 1,976 with significant 0,000 <0,05. Keywords: discipline, employee performance